(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The study is to determine the treatment used against pertussis in the city of Nasiriyah and compare it with treatments from international sources. based on data available from pectorlis service in Nasiriyah for whooping cough and compared with other antibiotic used by different sources on the basis on age group of patients ,effect and duration of antibiotics. drugs(Dexmethasone , Amoxicillin , ketotifenfumarate ) that used in AL- Nasiriyah and their effect . used as primary agents (Azithromycin ,Erythromycin ,clarithromycin ) and recommended antimicrobial that used as alternate agents trimethoprin with sulfamethoxazole (TMP-SMZ) . both by age group and use of antibiotics (clarithromycin ,Erythromycin ,Azithromycin, trimethoprin with sulfamethoxazole) for pertussis treat according to adult dose ,daily frequency and duration. treatment of pertussis in Nasiriyah has been shown to be inefficient compared to other sources.